Adubação foliar no desenvolvimento e nos aspectos fisiológicos, nutricionais e produtivos do cajueiro ‘BRS 226’ - Costa, Rafael Santiago da (2024)
Foliar fertilization is an interesting strategy for supplementing the nutrition of perennial plants and among the perennial crops highlighted in the Northeast, we have cashew tree with socioeconomic big importance. The dwarf cashew clone BRS '226' is widely used by farmers in the region, however, for this perform to its productive potential, it presents requirements in nutritional management, whether nutrients supplied via soil or foliar. In this sense, the present project aims to evaluate the effect of foliar fertilizers on the development, in the physiological, nutritional and productive aspects of adult plants of the dwarf cashew tree clone ‘BRS 226’. The experiment was conducted for three consecutive years (cycles) in the Experimental Field of Pacajus, belonging to Embrapa Agroindústria Tropical, located in Pacajus - CE. The design will be in randomized blocks with 5 treatments: four sources of foliar fertilizers (Master®; Mega 10®; FH CaB®; Master® + FH CaB®; Spray Dunger®) and control (without foliar fertilizer) and eight replications, totaling 40 experimental units, represented by an adult dwarf cashew tree. The growth variables were evaluated: plant height and crown diameter; physiological variables: gas exchange, chlorophyll a fluorescence and relative chlorophyll content; nutritional variables: macronutrients (N, P, K, Ca, Mg and S) and micronutrients (Cu, Fe, Zn, Mn and B); productive variables: development of maturis, percentage of ripe fruits and productivity of cashew nuts. The canopy volume (CV) was not influenced by the application of foliar fertilizers in any of the cycles evaluated. Plantas que receberam a adubação via foliar apresentaram maior taxa de crescimento relativo (TCR) ao longo dos ciclos, incrementando cerca de 113, 139 e 95%, quando comparado com o adubo foliar Master® + FH CaB® e tratamento controle. Gas exchange were increased by around 40% by foliar fertilization in all cycles, while the RCI increased by around 20% to 30%. Photochemical efficiency and macronutrient and micronutrient content were not influenced by foliar fertilization. The productive aspects were positively influenced by the application of foliar fertilizers, especially by the foliar fertilizer Master® + FH CaB®. The complementary use of foliar fertilizers was an efficient strategy to increase gas exchange, IRC and productive aspects. The multivariate analysis demonstrates that the biometric, physiological and nutritional aspects present a high correlation in the three cycles evaluated, being especially influenced by the Master® + FH CaB® and FH CaB® fertilizers.